Connecting objects, communities and cultural knowledge. Issue 1 (2nd January 2016) - Lewincamp, Sophie; Sloggett, Robyn
Abstract : Cultural objects carry forward the identity of the past into the future. The process of preservation therefore has strong impact on the transmission of cultural knowledge and the definition of identity. The works of Elman Service, Nicholas Thomas and Marica Pointon have examined concepts of geography, economics and politics to argue how, as custodians of cultural artefacts, cultural institutions can reframe the idea of authority knowledge. Informed by this work, and the broader critique of cultural positions by Arjun Appadurai and others, institutions have sought to enhance knowledge and presentations by engagement with collection-specific expert knowledge holders within communities, and, in so doing, to democratise the representation of cultural material. Defined initially by Mary Louise Pratt and later James Clifford, contact zones have been utilised within museums to create shared spaces for dialogue and exchange. Focusing on two case studies, the Returned and Services League LifeCare War Museum in Narrabeen and the Middle Eastern Manuscript Collection at the University of Melbourne, this paper examines how academic specialist knowledge in cultural materials conservation can be aligned with the needs of community-focused museums to enhance knowledge and understanding of the collection, and its conservation needs, through specialist expertise held by communities. It does so by examining how different zones—the initial landing zone, the early exploration zone, the collaboration zone and the transfer of knowledge zone—provide opportunities for potent interactions and complex creative exchanges.